Prospective survey of discrimination in pregnant persons and correlation with unplanned healthcare utilization - Greenberg, Rachel; Anguzu, Ronald; Jaeke, Elisha; Palatnik, Anna (American Journal of Obstetrics & Gynecology, 2023)
This was a prospective cohort study of pregnant persons receiving care at a single Midwestern academic institution from 2021 to 2022. Primary data was collected from participants on sociodemographic factors and on Perceived Ethnic and Discrimination Questionnaire (PED-Q), a validated 17-item scale measuring perceived lifetime interpersonal racial and ethnic discrimination in four domains: work/school, social exclusion, stigmatization, and threat. The primary outcome was unplanned healthcare utilization, defined as unplanned labor and delivery admissions, triage, Emergency Department, or urgent care visits. Bivariate and multivariate analyses were done to examine the association between lifetime exposure to discrimination and unplanned healthcare utilization.
Keywords: Unplanned healthcare utilization; Correlation; Pregnant persons